PENGEMBANGAN MOBILE LEARNING PENDIDIKAN AGAMA ISLAM BERBASIS ANDROID UNTUK PENGUATAN KARAKTER RELIGIUS DAN HASIL BELAJAR SISWA - Muhamad Muslihudin; Satriya Berland Atmaja (YHMM PUBLISHING, 2026)
The rapid development of information technology in the digital era has significantly influenced the education sector, including Islamic Religious Education (PAI). However, the learning process of PAI at MTs Muhammadiyah 1 Kalirejo is still dominated by conventional methods, resulting in students being less active, easily bored, and lacking learning motivation. This issue highlights the need for an innovative and interactive learning medium that aligns with current technological advancements. This study aims to design and develop an Android-based Islamic Religious Education learning application to enhance students’ learning motivation, effectiveness, and independence. The research adopts the Waterfall software development model, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. the results show that the developed application features curriculum-based learning materials, instructional videos, daily prayers, and interactive game-based quizzes with an integrated automatic evaluation system. Based on black-box testing, all functions operated properly according to the design. Furthermore, user evaluation through a questionnaire involving 20 respondents indicated an overall satisfaction rate of 86%, categorized as very good in terms of interface design, security, and usability. in conclusion, this Android-based PAI learning application serves as an innovative solution to improve learning effectiveness and student engagement, while supporting the digital transformation of education in Islamic schools.